1996
DOI: 10.1095/biolreprod55.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Membrane Integrity, Cytoskeletal Structure, and Developmental Potential of Murine Oocytes after Vitrification in Ethylene Glycol1

Abstract: A systematic approach was taken to assess and optimize a protocol for intracellular vitrification by introducing high concentrations of the cryoprotectant agent (CPA) ethylene glycol (EG) into unfertilized murine oocytes. The effects of EG on membrane integrity, microfilament organization, and developmental potential were evaluated. During exposure to 0.5-2 M EG, oocytes showed maximum shrinkage to 55.5% of the isotonic volume within the first minute and reexpanded to their initial volume within 15 min. Transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 29 publications
0
38
0
7
Order By: Relevance
“…Due to their large molecular size, sucrose could cause an osmotic gradient across the cell membrane, which enhances dehydration of the cell before freezing of extracellular water. In addition, it is suggested that sucrose is capable of preserving the structural and functional integrity of cell membranes at low water activities [29]. Sucrose, as nonpermeating cryoprotectants, has been used in the vitrification of ovarian tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their large molecular size, sucrose could cause an osmotic gradient across the cell membrane, which enhances dehydration of the cell before freezing of extracellular water. In addition, it is suggested that sucrose is capable of preserving the structural and functional integrity of cell membranes at low water activities [29]. Sucrose, as nonpermeating cryoprotectants, has been used in the vitrification of ovarian tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of carbohydrates to permeable cryoprotectants aids the dehydration of embryos (Kuleshova et al, 1999). It has been suggested that sugars are capable of preserving the structural and functional integrity of membranes at low water activity (Crowe, Carpenter, Crowe, & Anchordoguy, 1990;Hotamisligil, Toner, & Powers, 1996). The design of proper protocol for cryoprotectant incorporation is decisive for the success of cryopreservation, but adequate freezing/thawing rates are also necessary (Cabrita et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Variações térmicas muito abruptas podem interferir no transporte de água através da membrana celular e propiciar a formação de cristais de gelo e depósitos de sais no interior da célula 11 . Também as diferenças de pressão osmótica entre o ambiente intra e o extracelular podem levar à mudança de volume no oócito, com conseqüente dano na membrana plasmática e nas organelas 12 . Além disso, também tem sido demonstrado que o congelamento pode danifi car o citoesqueleto dos folículos antrais, com prejuízo no tráfego de moléculas e organelas no processo de divisão celular 13 .…”
Section: Criopreservaçãounclassified